2021
DOI: 10.1007/s40615-021-01129-x
|View full text |Cite
|
Sign up to set email alerts
|

Latinos’ Conceptualization of Depression, Diabetes, and Mental Health–Related Stigma

Abstract: Depression and diabetes are two of the most common health conditions experienced by those from Latino backgrounds. However, community-based stigma toward these health conditions may discourage those experiencing symptoms of depression or diabetes from seeking professional assistance. To assess stigma in the Latino community toward these common health conditions, a community-based sample of 469 Latino participants in a major urban area in the [Southwestern United States -Houston, TX] completed a face-to-face su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Stigmatization has been found to be strongly and consistently associated with negative psychological conditions, and it has been suggested that DM stigma is likely to have pervasive emotional, social, and cognitive impacts. 8,34 Also, as expected, 18,19 small negative correlations were found with the years of diabetes duration, which was evidence of the discriminant validity. In addition, the internal consistency of the scale was satisfactory, ranging from 0.80 to 0.89, and is in line with that of the original DSAS-1 18 and the Danish version ofit.…”
Section: Discussionsupporting
confidence: 79%
“…Stigmatization has been found to be strongly and consistently associated with negative psychological conditions, and it has been suggested that DM stigma is likely to have pervasive emotional, social, and cognitive impacts. 8,34 Also, as expected, 18,19 small negative correlations were found with the years of diabetes duration, which was evidence of the discriminant validity. In addition, the internal consistency of the scale was satisfactory, ranging from 0.80 to 0.89, and is in line with that of the original DSAS-1 18 and the Danish version ofit.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, professional organizations must endeavor to present positive portrayals of mental health services providers in Latino communities, and testimonials from Latino individuals who have found mental health services helpful. These steps can improve the therapeutic interaction and relationships that mental health providers have with their patients (Reynders et al, 2014; Washburn et al, 2022). The overall effect will be a reduction in mental health conditions in Latino communities, and a healthier workforce.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who "complain" about fulfilling social duties sometimes are regarded as weak, unable to bear suffering with courage and pride [46]. Additionally, the expectation to sacrifice oneself for the care of loved ones (marianismo) can further impact reports of depression due to the social stigma surrounding mental health issues and help-seeking behaviors [47]. For example, familism-the importance of placing family needs before individual interests-is valued to a greater degree in Latin America than in the U.S. [24].…”
Section: Discussionmentioning
confidence: 99%